Modeling Sustainable Development in Macroeconomic Models of Poland's National Economy - Florczak, Waldemar (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Socio-economic development of the contemporary world – and consequently: of particular national economies – is becoming a function of more and more conditions, among which are such that used to remain on the outskirts of economics, being rather an object of interests of other social sciences. The growing complexity of today's world is best grasped by the concept of sustainability. That is why all comprising models of the Polish economy should explicitly quantify selected aspects of sustainable development. This article presents proposals of extending the WSD-20Q model of the Polish economy – being the newest and adjusted version of a series of models called W8D. that have for years been constructed at the Chair of Econometric Models and Forecasts of the University of Lodz – by equations that would embrace selected, key aspects of sustainability. In effect, in the simulation version of the afore-mentioned model one could monitor non-economic conditions of socioeconomic development, as well as of their impact upon economic growth of Poland.